PROTECTIVE EFFECTS OF ETHYL ACETATE FRACTION OF Phaleria macrocarpa (Scheff) Boerl. ON OXIDATIVE STRESS ASSOCIATED WITH ALLOXAN-INDUCED DIABETIC RATS - Asih Triastuti; Jong Won Choi (Universitas Islam Indonesia, 2008)
ABSTRACTOxidative stress resulting from the increased production of reactive oxygen species playsa key role in the development of diabetes mellitus and its complications. Phaleria macrocarpa, atraditional plant from Indonesia, has been used empirically to control cancer, arthritis, and diabetesin society. The anti-diabetic effect and antioxidant activity of ethyl acetate (EtOAc) of Phaleriamacrocarpa (PM) was investigated in alloxan-induced diabetic rats. After two weeks administrationof PM, liver antioxidant enzyme and hyperglycemic state were evaluated. The result showed thatEtOAc fraction treatments reduced blood glucose levels in diabetic rats by oral administration(P